Rewriting the End: Narrative Reclamation and Posthuman Hope in MaddAddam - Tasnim, Zakiyah (Journal of Language and Literature Studies, 2025)
This article explores how Margaret Atwood’s MaddAddam (2013), the concluding volume of her speculative fiction trilogy, reconfigures post-apocalyptic narrative through storytelling, posthuman ethics, and interspecies kinship. Departing from the dystopian tone of Oryx and Crake and The Year of the Flood, MaddAddam turns toward cultural reconstruction and narrative continuity in the wake of ecological and societal collapse. The study adopts a qualitative, interpretive methodology rooted in close textual analysis, guided by posthumanist theory, feminist ecocriticism, and narrative theory. Particular attention is given to Toby’s reluctant but evolving role as storyteller, the Crakers’ reinterpretation of human memory into myth, and the novel’s depiction of interspecies alliances. The findings demonstrate that Atwood reframes survival not as individual endurance or technological mastery, but as a collective process of narrative reclamation. Storytelling emerges as an adaptive cultural practice that allows trauma to be processed, memory to be shared, and new ethical frameworks to be negotiated across human and nonhuman communities. The novel challenges anthropocentric hierarchies and patriarchal models of resilience, foregrounding instead relationality, care, and interdependence. It also illustrates how myth-making, far from being regressive, becomes a generative mode of continuity that sustains both human survivors and posthuman beings like the Crakers. Ultimately, MaddAddam refuses narrative closure, offering instead a vision of speculative regeneration in which memory, myth, and storytelling constitute the most enduring legacies of humanity. In doing so, Atwood positions narrative itself as a vital resource for imagining livable futures in the aftermath of catastrophe.